Persistent plus Disease after Laser in Retinopathy of Prematurity with Tetralogy of Fallot. Issue 5 (September 2013) - Paulus, Yannis M.; Moshfeghi, Darius M.
Purpose: We present a patient with retinopathy of prematurity (ROP) who received panretinal photocoagulation (PRP), but in whom plus disease developed, likely secondary to a complicated cardiovascular history, including DiGeorge syndrome and tetralogy of Fallot . Methods: Interventional case report with clinical and angiographic correlation . Results: Our patient had been born at 29 weeks and 2 days gestational age with a birthweight of 940 grams, tetralogy of Fallot, DiGeorge syndrome, and major aortopulmonary collaterals. Type 1 Early Treatment for Retinopathy of Prematurity ROP (zone 2, stage 2 with plus) developed, requiring PRP. Worsening plus disease developed and mild further PRP was performed. Despite this, plus disease persisted . Conclusions: We report plus disease even after appropriate PRP therapy for ROP. In this case, it is likely the patient's cardiovascular diseases that caused the persistent plus disease. Vascular tortuosity can be due to a number of different systemic disorders, so it is important to consider an infant's systemic conditions in the evaluation of ROP .